Ação moduladora do cortisol e da Aloe vera no sistema imune inato de peixes - Zanuzzo, Fábio Sabbadin [UNESP] (2014)
Immunostimulants have been used as alternative to prevent disease outbreaks in fish farm. Products derived from Aloe vera are popular around the world due to their medicinal properties, including immunostimulatory, and represent potentially an inexpensive alternative for the control of fish diseases. The purpose was to evaluate A. vera effects in stress and innate immune responses of pacu (Piaractus mesopotamicus), fish of economic value in Brazilian farming. Fish were fed, for 10 days, with four diets: control diet, and diets with 5 g kg-1 (0.5%), 10 g kg-1 (1%) and 20 g kg-1 (2%) of A. vera. Thereafter, fish were transported for 4 hours (166 g L-1) (Experiment 1) and then experimentally infected with Aeromonas hydrophila or injected with PBS buffer (sham), by intraperitoneal via (IP) (Experiment 2). Fish were sampled at the initial condition (before transport, n=10), transport arrival (n=11), 12 and 24 hours after transport without IP (Recovery; n=8) and also at 12 and 24 hours after transports with IP (Challenge; A. hyd. or PBS, n=8). Transport increased the cortisol and glucose levels and reduced the leukocyte respiratory burst (LRB) and hemolytic activity of alternative complement pathway (ACH) of control fish, while A. vera prevented the LRB and ACH reduction at arrival. Serum lysozyme concentration (SLC) increased at 24 h after transport in A. vera infected fish. LRB, SLC and ACH of fish feeding A. vera (2%) were significantly higher, 24 h after the bacterial infection, than in control fish. A. vera enhanced the innate immune responses tested in pacu and reinforces the possibility for medicinal herbs added to fish food as an alternative method to prevent diseases in fish